2016
DOI: 10.1016/j.pmrj.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Functionality and Usability of Two Novel Wheelchair Anti‐Rollback Devices for Ramp Ascent in Manual Wheelchair Users With Spinal Cord Injury

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Figure 6 shows the pooled prevalence of wrist pain in wheelchair users, following the meta-analysis of four available studies [ 11 , 25 , 29 , 31 ]. The pooled prevalence was 23% (95% CI 10–47%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 shows the pooled prevalence of wrist pain in wheelchair users, following the meta-analysis of four available studies [ 11 , 25 , 29 , 31 ]. The pooled prevalence was 23% (95% CI 10–47%).…”
Section: Resultsmentioning
confidence: 99%
“…Elbow [ 11 , 12 , 25 , 29 ], forearm [ 25 ], wrist [ 11 , 25 , 29 , 31 ] and hand pain [ 11 , 25 , 29 ] occurs as a result of overuse during propulsion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheelchairs facilitate access by users in the community. However, according to the 2011 Wheelchair Safety Accident Survey Report, 65.2% of users reported that they experienced pressure sores due to sitting for a long time [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Quebec User Evaluation of Satisfaction with Assistive Technology obtains user feedback on their satisfaction with any assistive device (Demers et al 2002 ). It can and has been used in comparative effectiveness studies assessing user satisfaction with assistive technology (Deems-Dluhy et al 2016 ; Sadiya, Pattnaik & Mohanty 2016 ). However, it is not a physical performance measure and does not supply information specific to wheelchair mobility.…”
Section: Introductionmentioning
confidence: 99%